Enterprise UNIONISM in crisis in Japan - Suzuki, Hiromasa (2004)
During the last decades, the unionization rate in Japan has been decreasing, while new forms of employment and outsourcing practices are imposed. In this context, the author analyses whether trade unions can continue to be considered legitimate representatives of workers and if they are responding to their aspirations. The first part of the work examines the achievements of trade unionism in companies between 1945 and 1980, while the second part exposes the problem areas identified since in 1991 the economic conditions of Japan changed substantially as a result of global competition and, in As a consequence, the companies restructured their activities, which included a reduction in employment and new locations in China.